EFFICACY AND SAFETY OF THE INFLUENZA VACCINE AMONG CHILDREN WITH DIFFERENT HEALTH CONDITIONS - M.G. Galitskaya (Вопросы современной педиатрии, 2007)
Efficacy and safety of vaccine «Grippol» among children with different health status was analyzed. The most efficacy of the influenza vaccine revealed in the group of children with compromised health status, as well as in the group of allergic children. The safety of influenza vaccination was confirmed in children with different health conditions.Key words: children, vaccination, influenza, efficacy, safety.